An Investigation into the Adsorption of Aniline from Aqueous Solution Using H-Beta Zeolites and Copper-Exchanged Beta Zeolites - J. O'Brien; T. Curtin; T.F. O'Dwyer (Adsorption Science & Technology)
Zeolite beta, a large-pore zeolite, was investigated in this study with a view to examining it as a potential adsorbent for the removal of aniline from aqueous solutions. Two different metal-loaded zeolites were prepared by exchanging H-beta zeolite (SiO 2 /Al 2 O 3 = 75:1) with copper. The influence of exchanged copper on the uptake level was assessed. The effect of varying the silica-to-alumina ratio of the H-beta zeolite on the aniline uptake level was also examined, using three different H-beta zeolites with ratios of 25:1, 75:1 and 150:1 as adsorbents. The sorption experiments indicated an uptake level of ca. 110–120 mg/g for each zeolite and this level was also adsorbed by the copper-modified H-beta zeolites (SiO 2 /Al 2 O 3 = 75:1). In all cases, the adsorption process followed the Langmuir model for adsorption and the level of aniline adsorbed was largely unaffected by a change in temperature or the presence of extra framework copper. The stability of the exchanged copper on these zeolites was then examined by measuring the quantity of copper leached from each zeolite into solution as a function of pH. Minimum copper leaching was observed in the pH range 5–11. This provided a stable pH working range for the adsorbent materials.